Performance analysis of Savonius wind turbines in different models. Issue 5 (October 2022) - Simsek, Ayse; Teksin, Suleyman; Akansu, Selahaddin Orhan; Akansu, Yahya Erkan
This study presents experimental results of power performance characterizations for of 12 different Savonius turbine blades. There are three different models and the numbers of each blade types have been selected as 2, 3, 4, and 5. Three different blade types are drawn in a CAD program and all blade models are produced from 3D printer. The experiments are carried out in the subsonic wind tunnel laboratory of the Faculty of Aeronautics and Astronautics at Erciyes University. The wind tunnel has 15 kW motor power to produce wind flow. Test zone inlet and outlet section is 0.57 m × 0.57 m and 0.59 m × 0.59 m respectively. Shaft to shaft type torque meter is mounted between turbine and electric motor. Measurements have been made at wind speeds between 1 and 30 m/s. The performance values of each turbine have been measured. While the 3-bladed turbine showed the highest power coefficient values in the whole study, the maximum value was obtained from the modified helical turbine type.